Market discipline and regulatory arbitrage: Evidence from ABCP liquidity guarantors - Chen, Jiakai (Journal of Banking & Finance, 2022)
We investigate whether the U.S. stock market disciplines asset-backed commercial paper (ABCP) liquidity guarantors who exploit a regulatory loophole that exempts at least 90% of the risk capital charge. We find that the market reduces liquidity guarantors’ franchise value when a short ABCP maturity causes the conduit credit losses to remain with guarantors rather than being transferred to investors. Banks with franchise value more sensitive to the ABCP guarantee cost maintain a higher risk capital buffer. We interpret our findings as evidence that market discipline–complexity of the shadow banking system notwithstanding–alleviates the consequence of regulatory arbitrage.